(untitled) (Comprehensive Journal of Science, 2026)
This study examines administrative governance and its impact on combating corruption. This study presents the concept of governance, its objectives, and the principles upon which it is based. It also examines the nature of corruption, its forms and causes, and the mechanisms for combating it. It also examines how governance contributes to combating corruption and mitigating its effects. Corruption is considered one of the most serious challenges facing both developing and developed countries. Given its negative impact on economic, social, and political development, in the Libyan context, corruption has increased due to weak institutions, political instability, and the lack of effective enforcement and oversight. In this context, governance emerges as a fundamental mechanism aimed at promoting the principles of transparency, accountability, the rule of law, and community participation. This reduces the chances of corruption spreading and enhances the efficiency of public institutions. This research aims to shed light on the role of governance in combating corruption in Libya by analyzing the theoretical framework of the concepts of governance and corruption. It also examines the reality of the Libyan environment, presents corruption indicators from some countries, and compares them to Libya. It also examines the challenges facing these countries that prevent them from effectively implementing governance principles. One of the most important results reached by the research is that corporate governance reduces the risks of administrative and financial corruption in Libya, and that the application of governance rules contributes to enhancing the economic stability of government and investment projects in various fields. The study recommended holding seminars and conferences to introduce the governance system and its importance, providing the necessary requirements for its implementation, benefiting from international experiences in combating corruption, focusing on implementing governance principles, and forming a higher national committee to monitor implementation, with the involvement of experts and representatives of civil society to ensure transparency and credibility.